Para uma andragogia do esporte:discutindo as diretrizes e a formação profissional para a Educação Física de Jovens e Adultos - Chacon Filho, ágrio de Oliveira (2007)
For the development of this research the following general objective has been formulated, indicator of the process of inquiry: To discuss the relation between the attitudinal and the sportive contents presented in the proposal of Curricular Lines for the Physical Education of Young and Adults in Brazil. According to the corporeity and the ludicity, questioning the formation of the professional of Physical Education and delineating the perspective for a sport andragogy that values the Being and the Life. From this general objective, the following objectives, which had given greater specificity to the investigative process, were defined: 1. To create the theoretical context from the corporeity/ludicity axis, articulating transversally sportive knowledge, aiming to contribute for a sport Andragogy; 2. To analyze the objectives proposed for the Physical Education of Young and Adults according to an elaborated theoretical reference and to the testimonies of the egresses of 2005 of the Physical Education course of the UFRN. 3. To interpret the relation between attitudinal and educative content from the academic reality lived by the egresses of the Physical Education course of the UFRN. 4. To understand the most urgent necessities of sustained formation of the egresses of 2005 for satisfactory performance with the Physical Education of Young and Adults. 5. To propose perspectives for the construction of a sport Andragogy from the corporeity/ludicity axis. In attendance to the nature of this research and as form of guiding ourselves in this epistemological adventure, the following ones had been basically and theoretically estimated. 1. Corporeity is a radiant focus, prime and main of educational criteria; 2. The task of the education must be carried through with men and not for men; 3. Man must only play with the beauty and with the beauty he only must play. ; 4. The sportive education must be based on esthetic and fair play. The adopted research approach is of a qualitative nature, using the interview procedure with a group consisting of twelve egresses of the Physical Education Course of the UFRN of the year of 2005.2 After the discussion of the results on the attitudinal objectives and content for the Physical Education for Adults and Young, the study shows nine themes presented by the investigated group as priorities for their sustained formation, aiming at the performance of the professional of Physical Education with the EJA: inclusive experiences; leisure and quality of life; relationships; body and personal care; social values; self esteem; sportive phenomenon; EJA training; attitudinal contents. As a contribution to the construction of knowledge for a Andragogy of Sports, the study presents a metaphorical structure called Galaxy of Knowledge righteous Glamor of integrating nine elements inspired by the Ode to the Sport of Pierre de Coubertin: life, beauty, justice, daring, honesty, joy; Fertility; progress; peace. At the heart of the structure of knowledge is righteous install a system that articulates five principles ludopoiético epistemological function of connecting with the righteous knowledge of the sport that must integrate the content attitudinal proposed for Fitness for Youth and Adults in order to facilitate the realization of their objectives proposed for this method of teaching